2022
DOI: 10.3389/fmicb.2022.1050372
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming increases fungal alpha diversity in an oligotrophic maritime Antarctic soil

Abstract: The climate of maritime Antarctica has altered since the 1950s. However, the effects of increased temperature, precipitation and organic carbon and nitrogen availability on the fungal communities inhabiting the barren and oligotrophic fellfield soils that are widespread across the region are poorly understood. Here, we test how warming with open top chambers (OTCs), irrigation and the organic substrates glucose, glycine and tryptone soy broth (TSB) influence a fungal community inhabiting an oligotrophic mariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
2
4
0
Order By: Relevance
“…Interestingly, in addition to other abiotic parameters known to determine the abundance of soil fungal taxa in Antarctica, such as soil texture and cation concentrations (Canini et al, 2020, 2021; Connell et al, 2006), soil C and N concentrations also strongly affected the abundances of fungi and, as revealed by the PCA analysis, were discriminant variables separating soil samples. In agreement with studies showing increased abundances of yeasts in nutrient‐amended oligotrophic Antarctic soils (Newsham et al, 2022), two genera of yeasts, Naganishia and Meyerozyma , the main constituents of the soil fungal communities at the three study sites, showed positive correlations with cation concentrations in soil. These data confirm previous studies showing soil cation concentrations affect the richness and composition of Antarctic soil fungal communities (Canini et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, in addition to other abiotic parameters known to determine the abundance of soil fungal taxa in Antarctica, such as soil texture and cation concentrations (Canini et al, 2020, 2021; Connell et al, 2006), soil C and N concentrations also strongly affected the abundances of fungi and, as revealed by the PCA analysis, were discriminant variables separating soil samples. In agreement with studies showing increased abundances of yeasts in nutrient‐amended oligotrophic Antarctic soils (Newsham et al, 2022), two genera of yeasts, Naganishia and Meyerozyma , the main constituents of the soil fungal communities at the three study sites, showed positive correlations with cation concentrations in soil. These data confirm previous studies showing soil cation concentrations affect the richness and composition of Antarctic soil fungal communities (Canini et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, previous studies of soil fungal diversity in Antarctica have typically been carried out using culturing methods (Arenz & Blanchette, 2011;Connell et al, 2008). Many recent studies using cutting-edge molecular techniques have been focused on the Maritime Antarctic (see for example, da Silva et al, 2020;Dur an et al, 2019;Newsham et al, 2021Newsham et al, , 2022Rosa et al, 2020;Santos et al, 2020) or coastal sites in continental Antarctica (Canini et al, 2020;Ji et al, 2016;Siciliano et al, 2014), and with comparatively few studies using these techniques on inner continental Antarctic fungal communities. The handful of molecular mycological studies hitherto carried out in inner continental Antarctica have revealed the dominance of a narrow range of fungal taxa in soils, primarily belonging to Ascomycota and Basidiomycota, with the latter mainly being represented by yeasts (Arenz et al, 2014;Pudasaini et al, 2017;Wei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We anticipated that, as in vegetated Arctic soils, warming and irrigation would rapidly affect the rates of exchange of greenhouse gases between the atmosphere and soil [ 23 , 24 ]. However, in contrast with the majority of studies on densely vegetated Arctic soils [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], but in accordance with those on barren soils in maritime Antarctica [ 25 , 26 , 27 ], we anticipated rapid treatment effects on the size and composition of the soil microbial community.…”
Section: Introductionsupporting
confidence: 46%
“…In agreement with previous studies on Arctic soils [ 23 , 44 , 45 , 46 ], we found that a 1 °C rise in summertime near-surface temperature in a sparsely vegetated patterned ground soil on Svalbard increased soil CO 2 efflux and CH 4 consumption rates after 4 years of treatment. However, in contrast with experiments on vegetated soils in the Arctic [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], but in accordance with those on barren maritime Antarctic soils [ 25 , 26 , 27 ], rapid impacts of the warming treatment on the size and composition of the soil microbial community were recorded. Other than a marginally significant positive effect on CO 2 efflux, irrigation had no effects on greenhouse gas flux rates or the soil microbial community.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation